Joint attention skills in wild Arabian babblers (Turdoides squamiceps): a consequence of cooperative breeding?. Issue 1900 (3rd April 2019) - Ben Mocha, Yitzchak; Mundry, Roger; Pika, Simone
Abstract : Human cooperation strongly relies on the ability of interlocutors to coordinate each other's attentional state: joint attention. One predominant hypothesis postulates that this hallmark of the unique cognitive system of humans evolved due to the combination of an ape-like cognitive system and the prosocial motives that facilitate cooperative breeding. Here, we tested this hypothesis by investigating communicative interactions of a cooperatively breeding bird species, the Arabian babbler ( Turdoides squamiceps ). The behaviour of 12 wild social groups was observed focusing on two distinct communicative behaviours:object presentation andbabbler walk . The results showed that both behaviours fulfilled the criteria for first-order intentional communication and involved co-orientation of recipients' attention. In turn, recipients responded with cooperative and communicative acts that resulted in coordinated joint travel between interlocutors. These findings provide the first evidence that another animal species shows several key criteria traditionally used to infer joint attention in prelinguistic human infants. Furthermore, they emphasize the influence of cooperative breeding on sophisticated socio-cognitive performances, while questioning the necessity of an ape-like cognitive system underlying joint attentional behaviour.